Factors Associated with Pneumonia Incidence in Toddlers in the Pediatric Ward of RSUD Kudungga Kutai Timur - Fitri Ratnasari; Sutrisno Sutrisno; Nilam Noorma (Asian Journal of Social and Humanities, 2023)
Pneumonia is one of the infectious diseases that attacks the lower respiratory tract, which is characterized by coughing, and shortness of breath. Risk factors that increase the morbidity and mortality of pneumonia are divided into two major groups, namely intrinsic factors and extrinsic factors. Intrinsic factors include age, gender, nutritional status, low birth weight, immunization status, breastfeeding, and vitamin A administration. Extrinsic factors include residential density, ventilation, air pollution, humidity, cigarette smoke, family income and maternal factors, both education, mother's age, and mother's knowledge. The aim of the study was to determine the factors associated with the incidence of pneumonia in toddlers in the Children's Room of Kudungga Hospital, East Kutai. This study uses a correlation research design with a cross-sectional research design. The sample in this study was 57 people. The results of statistical tests using the chi-square test obtained p-value = 0.000 (knowledge), p-value = 0.001 (immunization status), p-value = 0.000 (nutritional status) and p-value = 0.000 (smoking history). There is a relationship between knowledge, immunization status, nutritional status and family history of smoking with the incidence of pneumonia in toddlers in the Children's Room of Kudungga Hospital, East Kutai.